Spectroscopic Studies of Minerals in Some Indian Coals - Saikia, B.K. (Asian Journal of Chemistry, 2010)
Far-infrared spectra of the range, 400-200 cm-l were recorded for eight different high sulphur coal samples from Assam (India) for the first time. The observed unusual spectral bands are accounts for the minerals viz., kaolinite, calcite, magnesite, illite, siderite, pyrite present in the coals.